The legal culture of the European Court of Human Rights - Arold Lorenz, Nina-Louisa. (Leiden, Netherlands ; Boston : Martinus Nijhoff Publishers, 2007)
Without understanding the legal culture of the judges a full understanding of Strasbourg's rulings seems hardly possible. Through interviews, field observations and case law analysis, this book aims to fill this need and offers a fresh approach towards convergence in Europe.
Introduction: the jigsaw puzzle of Europe -- Background of the court from its creation to its enlargement -- Administration of justice -- Attitudes and dynamics amongst the judges -- Testing the legal culture of the court -- Conclusion.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: European Court of Human Rights; European Court of Human Rights; Human rights -- Europe; Judges -- Europe; Judicial opinions -- Europe; Justice, Administration of -- Europe; Court administration -- Europe; Droits de l'homme (Droit international) -- Europe; Jugements -- Europe; Tribunaux -- Administration -- Europe; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Court administration; Human rights; Judges; Judicial opinions; Justice, Administration of; Europe